Regulatory and legal mechanism of development and realization of policy to preserve cultural and historical heritage sites of St. Petersburg - K. R. Paliy (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Historical and cultural heritage ofSt. Petersburgis the most important constituent of socio-economic and spiritual potential of the city. Present institutions are not able to prevent negative damaging of the cultural heritage sites trend. Public organizations and patrons of art are not given enough attention.The article describes some features of government policies on preservation of cultural heritage sites. The problems of developing political and legal mechanisms for regulating the preservation and development of the historical and cultural heritage ofSt. Petersburghave been identified and the town-planning factor in the system of cultural heritage protection has been analyzed. According to the results of the detected problems, recommendations aimed at the improving the protection system for historical and cultural monuments ofSt. Petersburgwere formulated. The development of the cultural heritage protection system can be promoted by an integrated approach, built on the interaction of social, economic, urban and political structures.